Individual and environmental factors associated with park and plaza use in adults from Curitiba, Brazil. DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p377 - Ana Carina Cassou; Rodrigo Siqueira Reis; Rogério César Fermino (Universidade Federal de Santa Catarina, 2012)
DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p377The aim of this study was to identify individual and environmental factors associated with park and plaza use in adults from Curitiba, state of Paraná, Brazil. A cross-sectional study was conducted in 2008 with 749 participants (59.9% men) selected in areas for physical activity (PA) in four parks and four plazas. Poisson regression was used to examine the associations of sociodemographic (sex, age, education) and health (body mass index, perceived health) variables, company for park/plaza use, access (perception of distance, access and commuting to the places), and leisure time PA (walking and moderate/ vigorous PA - MVPA) with frequent use of parks and plazas (≥1 time/wk). The percentage of park and plaza use was 68%, and company (PR: 0.74; CI95%: 0.62-0.89) and higher levels of walking (PR: 1.30; CI95%: 1.03-1.64) and MVPA (PR: 1.39, CI95%: 1.07-1.80) were associated with the use of the places. These results can be used to guide interventions aimed at providing services and facilities for PA practice in parks and plazas.